Hepatitis B and HIV in Children and Pregnant Ladies at Patan Hospital - Ansari, Imran (Journal of Patan Academy of Health Sciences, 2015)
Introductions: The primary objective of this study was to find the prevalence of Hepatitis B and HIV infections in children and pregnant ladies visiting Patan Hospital. The secondary objective wasto investigate how these individuals may have got infected, the clinical presentation and outcome. Methods: Laboratory records of all individuals tested for Hepatitis B and HIV between 2006 July to 2011 Aug were included. The charts were reviewed for history and clinical findings Results: Out of 44,958 individuals who were tested, 229 were positive. The prevalence of HIV was 0.2% and HBV 0.3% and both was 0.01% (5). The numbers of children under age of 15 and of pregnant ladies were 13 and 32 respectively. Risk factors identified in 40 adult patients were: intravenous drug use, multiple sex partners, working abroad and long distance drivers. Twenty-seven patients died, all with HIV. Of the 32 pregnant ladies 31 were discovered by routine testing. All the babies born were healthy. Fever, cough and breathing difficulty were the most common presenting features. Ten were treated for pneumonia and 3 for TB. Parents of 5 HIV-infected infants also had the same infection themselves. There was no death among children. Conclusions: The prevalence of HBV and HIV was low. HBV was a ‘hidden’ infection, discovered on routine testing of asymptomatic pregnant ladies. Almost all children got these infections through vertical transmission. Plain Language Summary: This study was conducted to see prevalence of Hepatitis B and HIV in pregnant ladies and children at Patan Hospital, Nepal. Charts were reviewed. Prevalence of both was found to be very low. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13012 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):26-29